Megistos : a world income and trade model for the 1975 - Duprez, Colette; Kirschen, Etienne Sadi. (Amsterdam : North-Holland Pub. Co. ; New York : American Elsevier, 1970)
The title MEGISTOS- the superlative of the Greek word for large - is meant to convey the idea of economic magnitudes taken at the world level or nearly, and thus larger than the macro-variables generally considered in national economic models.
"List of countries belonging to each zone": fold. leaf inserted.
Includes bibliographical references and index.
rpm 25/01/2019
Loans
Keywords: Commerce; Economic development